Case Report: Intraocular foreign body coexisting for 30 years - Zhu, Rong; Wang, Chong; Gu, Zhensheng (Frontiers in Medicine, 2025)
BackgroundThe majority of IOFBs remain in the posterior segment and those in the anterior chamber are uncommon. We report a case of IOFBs in the anterior chamber for 30 years without any symptoms.Case presentationThe case involves a 30-year-old male individual who was told to have an abnormality in the anterior chamber of his left eye during a physical examination. However, the patient has had no any ocular discomfort symptom within the past 30 years. At the patient’s initial visit, the uncorrected visual acuity of the left eye was 40/50, the corneal endothelial surface exhibited multiple linear and curved scratches, and a transparent foreign body approximately 11 mm in length inhabited in the anterior chamber, touching the endothelium with fan-shaped ends, and the anterior chamber without any signs of inflammation. The endothelial cell count was 1,110 cells/mm2. Considered the persistent damage to the corneal endothelium caused by the foreign body, as well as the uncertainty regarding the path of entry and the characteristics of the foreign body, we surgically extracted the intraocular foreign body. No sight-threatening postoperative complications were noted.ConclusionA detailed history collection, a thorough physical examination and modern imaging techniques are beneficial for finding IOFBs. Asymptomatic anterior chamber foreign bodies may also cause potential corneal endothelium injury, which should be carefully examined and extracted using appropriate surgical methods to avoid iatrogenic injury.